Universal patterns of intervention: practice, no '-isms'. Issue 3 (4th May 2019) - Kühn, Florian P.
ABSTRACT: Widely used distinctions between national and international, between external and local, direct our view away from the political economy of classed interests guiding interventions. In Western and authoritarian interventions alike, such interests align across borders, calling into question the separateness of profiteers groups. Critiques of the liberal peace have overlooked how (capitalist) interests alloy the practice of interventions beyond norms, legitimation claims and international order; unless researchers turn to mapping the cross-connections of the global 'interventionist class', interventionism will not be fully understood.